Description of the Physical Condition of the Houses of Acute Respiratory Infection Sufferers - Imanuel Ruku; Wanti Wanti; Ragu Harming Kristina; Erika Maria Resi; Titik Respati; Isnawati Isnawati (Journal of Tropical Diseases and Health Science, 2023)
Acute Respiratory Tract Infection (ARI) is an infectious disease that attacks toddlers, children, and adults that occurs in the respiratory tract and is mostly a viral infection. One of the factors causing ARI is the physical condition of the house. The purpose of this study was to determine the physical condition of the houses of ARI sufferers in Tunbaun Village, West Amarasi District, Kupang Regency. This descriptive study was conducted by surveying the physical condition of the houses of ARI sufferers. The sample was 99 houses of ARI sufferers in Nunbaun Village in 2022. The research variables were lighting, ventilation, humidity, flooring, occupancy density, and temperature. This study found that the physical condition of the houses of ARI sufferers, the lighting variable, 21 houses (21%) met the requirements, and 78 houses (79%) did not meet the requirements. The ventilation variable, 68 houses (69%) met the requirements and 31 houses (31%) did not meet the requirements. The humidity variable, 38 houses (38%) met the requirements, and 61 houses (62%) did not meet the requirements. The floor condition variable met the requirements in 43 houses (43%), and did not meet the requirements in 56 houses (57%). Regarding the density of bedrooms of patients, 79 houses (80%) met the requirements, and 20 houses (20%) did not meet the requirements. The temperature variable was 11 houses (11%) met the requirements and 88 houses (89%) did not meet the requirements. Based on the results of this study, it is recommended that house floors are not made of earth, and cement floors must also be regularly cleaned. Residents should open windows to ensure optimum humidity and provide artificial ventilation.